1984
DOI: 10.1507/endocrj1954.31.55
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone response to human pancreatic growth hormone releasing factor in cattle.

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…On all the days of blood sampling a peak of endogenous GH was always registered, suggesting chronic GRF injections for 3 months did not cause any refractoriness of endogenous GH release. The GRF-induced GH response was also found to decrease with age in rats (Sonntag et al 1983, Ceda et al 1986, Cuttler et al 1986 and cattle (Johke et al 1984), and this decrease could be due to a decrease in sensitivity of somatotrophs to GRF with ageing (Ceda et al 1986), an increase in sensitivity of somatotrophs to somatostatin with ageing (Cuttler et al 1986) and/or to an age-related accumulation of somatostatin in somatotrophs (Brazeau et al 1986). …”
Section: Plasma Gh Changes Associated With Grf Administrationmentioning
confidence: 98%
“…On all the days of blood sampling a peak of endogenous GH was always registered, suggesting chronic GRF injections for 3 months did not cause any refractoriness of endogenous GH release. The GRF-induced GH response was also found to decrease with age in rats (Sonntag et al 1983, Ceda et al 1986, Cuttler et al 1986 and cattle (Johke et al 1984), and this decrease could be due to a decrease in sensitivity of somatotrophs to GRF with ageing (Ceda et al 1986), an increase in sensitivity of somatotrophs to somatostatin with ageing (Cuttler et al 1986) and/or to an age-related accumulation of somatostatin in somatotrophs (Brazeau et al 1986). …”
Section: Plasma Gh Changes Associated With Grf Administrationmentioning
confidence: 98%
“…These results demonstrated that both TRH and GRF could stimulate GH secretion in cattle, but nobody had studied the influence of these peptides on GH and IGF, release during the postnatal period in calves. It has been demonstrated that plasma GH response to GRF 1-44 in bovines decreases with age : the response observed in 4-month old calves was more intense than that measured in heifers or cows (Johke et al, 1984). In these animals as well as in our calves, GRF induced a marked rise in plasma GH concentration at all the doses studied (20 to 200 nmoles.kg-1 of body wt), and this elevation occurred within 10 min after injection (Johke et a/., 1984) (figs.…”
Section: Introductionmentioning
confidence: 94%
“…In these 10-day old animals, GRF GRF has been used to stimulate GH secretion in farm animals (Johke et al, 1984 ;McCutcheon et al, 1984 ;Moseley et al, 1984 ;Hodate, Johke and Ohaschi, 1985) so as to increase milk yield in cows (Enright et al, 1985 ; and ewes (Hart et al, 1985). Similarly, when GRF 1-29 was injected intravenously (0.2 nmoles.kg-' of body wt) six times per day for 10 days, cow milk yield increased by 16.1 % .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, exogenous human growth hormone-releasing factor (hGRF) specifically stimulates GH release in cattle (Johke et al, 1984;Moseley et al, 1984). Furthermore, it has been reported that exogenous hGRF (Enright et al, 1986;Pelletier et al, 1987;Lapierre et al, 1988) or bovine GRF (bGRF; Enright et al, 1988) increased milk production in dairy cows, and these increases in milk production are thought to be mediated by increased endogenous GH via hGRF or bGRF.…”
mentioning
confidence: 99%